Genomic and Evolutionary Analysis of Salmonella enterica Serovar Kentucky Sequence Type 198 Isolated From Livestock In East Africa - Saraiva, Mauro de Mesquita Sousa; Benevides, Valdinete Pereira; Silva, Núbia Michelle Vieira da; Varani, Alessandro de Mello; Freitas Neto, Oliveiro Caetano de; Berchieri, Ângelo; Delgado-Suárez, Enrique Jesús; Rocha, Alan Douglas de Lima; Eguale, Tadesse; Munyalo, Janet Agnes; Kariuki, Samuel; Gebreyes, Wondwossen Abebe; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Since its emergence in the beginning of the 90’s, multidrug-resistant (MDR) Salmonella enterica subsp. enterica serovar Kentucky has become a significant public health problem, especially in East Africa. This study aimed to investigate the antimicrobial resistance profile and the genotypic relatedness of Salmonella Kentucky isolated from animal sources in Ethiopia and Kenya (n=19). We also investigated population evolutionary dynamics through phylogenetic and pangenome analyses with additional publicly available Salmonella Kentucky ST198 genomes (n=229). All the 19 sequenced Salmonella Kentucky isolates were identified as ST198. Among these isolates, the predominant genotypic antimicrobial resistance profile observed in ten (59.7%) isolates included the aac(3)-Id, aadA7, strA-strB, blaTEM-1B, sul1, and tet(A) genes, which mediated resistance to gentamicin, streptomycin/spectinomycin, streptomycin, ampicillin, sulfamethoxazole and tetracycline, respectively; and gyrA and parC mutations associated to ciprofloxacin resistance. Four isolates harbored plasmid types Incl1 and/or Col8282; two of them carried both plasmids. Salmonella Pathogenicity islands (SPI-1 to SPI-5) were highly conserved in the 19 sequenced Salmonella Kentucky isolates. Moreover, at least one Pathogenicity Island (SPI 1–4, SPI 9 or C63PI) was identified among the 229 public Salmonella Kentucky genomes. The phylogenetic analysis revealed that almost all Salmonella Kentucky ST198 isolates (17/19) stemmed from a single strain that has accumulated ciprofloxacin resistance-mediating mutations. A total of 8,104 different genes were identified in a heterogenic and still open Salmonella Kentucky ST198 pangenome. Considering the virulence factors and antimicrobial resistance genes detected in Salmonella Kentucky, the implications of this pathogen to public health and the epidemiological drivers for its dissemination must be investigated.